The Laurentian Concept: A Review - Funk, R. E. (Archaeology of Eastern North America, 1988)
The 50-year history and changing definitions of the concept of the Laurentian tradition are reviewed. Extensive research since Ritchie's most recent discussion (1973) has revolutionized the understanding of the northeastern Archaic and the place of Laurentian in the Late Archaic period. Current evidence suggests that Laurentian, as presently defined, appeared about 5200 years ago but originated in a "Proto-Laurentian" complex over 6000 years ago. Laurentian is regarded as the oldest of the known Late Archaic traditions throughout the Northeast. Its multiple origins and marked geographic variability reflect complex and still dimly grasped adaptations to regional environments.
Keywords: anthropology